THE COMMUNICATION STRATEGY OF THE TELEGRAM CHANNEL ‘KAZAKHS IN BALI’ THE ROLE OF DIGITAL MEDIA IN STRATEGIC CULTURAL COMMUNICATION AMONG DIASPORAS - Aruzhan Tleuman; Fardiah Oktariani Lubis; Rastri Kusumaningrum (Journal of Innovation Research and Knowledge, 2025)
This study explores the communication strategy of the ‘Kazakh in Bali’ Telegram channel using the circular S.O.M.E (Share, Optimize, Manage, Engage) model as its theoretical framework. Through a qualitative approach, including interviews with the channel’s founder and content analysis, the research examines how the channel facilitates engagement and interaction within the Kazakhstani diaspora in Indonesia, particularly Bali. The findings reveal that the channel effectively shares relevant content, optimizes Telegram’s platform features, maintains organized management, and fosters member-led engagement, resulting in both virtual and real-world impacts. Activities initiated through the channel—such as cultural gatherings, domestic tourism, environmental volunteering, and charity work—not only strengthen community ties but also contribute positively to Indonesia. This research contributes to understanding how digital diaspora communities can serve as agents of cultural exchange and social contribution through strategic communication practices.